Applications of solar radiation pressure in orbital maneuvers - Geraldo Magela Couto Oliveira (2018)
The effects of the solar radiation pressure in the trajectories of a spacecraft in orbital transfers are studied. In a system formed by small bodies, the solar radiation pressure has a significant influence in the transfer paths. This occurs because the gravitational forces in these systems are smaller, if compared with systems formed by larger bodies. Solutions with lower and higher fuel consumption can be found by adding the solar radiation pressure. The solar radiation pressure is not used as a control but its effects over the transfers are measured and used in a natural form to get more economical transfers. For a small system of primaries such as an asteroid system, it was found that is very important to take into account this to make sure that the spacecraft will reach the desired points in the respective systems.